Evidence for Cardiomyopathy in Familial Diabetes Mellitus - Regan, Timothy J. (1977)
Recent epidemiologic studies have suggested that cardiac disease in common in diabetics and may often have a noncoronary basis. To examine the status of the left ventricle, 17 adult-onset diabetics of familial type without hypertension or obesity underwent hemodynamic study and were compared to 9 controls of similar age. Of the 17, 12 subjects had no significant occlusive lesions by coronary angiography. From this group eight without heart failure had a modest, but significant, elevation of left ventricular end-diastolic pressure. End-diastolic and stroke volumes were reduced, but ejection fraction and mean rate of fiber shortening were within normal limits. The left ventricular end-diastolic pressure/volume ratio was significantly higher than controls. Afterload increments effected a significant increase of filling pressure compared to normals without a stroke volume response, consistent with a preclinical cardiomyopathy. Four patients with prior heart failure had similar but more extensive abnormalities. None had local dyskinesia by angiography, and lactate production was not observed during pacing-induced tachycardia. Left ventricular biopsy in two patients without ventricular decompensation showed interstitial collagen deposition with relatively normal muscle cells. These findings suggest a myopathic process without ischemia. Postmortem studies were performed in 11 uncomplicated diabetics. Nine were without significant obstructive disease of the proximal coronary arteries, and the majority succumbed with cardiac failure. On left ventricular sections, none had evident luminal narrowing of the intramural vessels. All nine exhibited periodic acid-Schiff-positive material in the interstitium. Collagen accumulation was present in perivascular loci, between myofibers, or as replacement fibrosis. Multiple samples of left ventricle and septum revealed enhanced triglyceride and cholesterol concentrations, as compared to controls. Thus, a diffuse extravascular abnormality may be a basis for cardiomyopathic features in diabetes.